The News Coverage of Saudi Women Driving Restriction: A Comparative Analysis of Modality in Al-Jazirah News Reports of Restriction and Post Restriction Era - Farah Nadia Harun; Muhammad Marwan Ismail; Nurhasma Muhammad Saad; Wan Moharani Mohammad; Zulkipli Md. Isa (Asian Scholars Network, 2026)
Indexed by MyCite